Non hydrazine based chemical synthesis of earth abundant Cu2SnS3 thin film photocatalyst for wastewater treatment. Issue 12 (15th June 2023) - Zaman, M Burhanuz; Shrotriya, Vipin; Hossain, Amzad; Mehedi, Ibrahim M.; Alam, Md. Mottahir
Abstract: Utilization of renewable solar energy has been a vital achievement for material scientists. The present work represents synthesis of Cu2 SnS3 (CTS) thin film photocatalysts by a simple and economical spin coating sol gel method. The films were investigated for their structural, morphological, compositional, optical and chemical properties. Monoethanolamine (MEA) was employed to enhance the age of CTS gel by increasing its stability. X-ray diffraction (XRD) and Raman analysis indicated formation of single phase pristine tetragonal CTS material. Morphological studies showed the films are covered with CTS quantum dots. X-ray photoelectron spectroscopy (XPS) revealed oxidation states of Cu, Sn and S as +1, +4 and −2 respectively. The CTS material exhibited polycrystalline nature determined from the selected area electron diffraction (SAED) patterns of the films. The films has optimum energy band gap (∼1.7 eV) suitable for visible light photocatalysis. The thin films were explored as photocatalysts against methylene blue (MB) dye and it was found that the films degraded most of the dye (∼87%) in just 90 min of visible light illumination. Reusability experiments performed showed the films can be used again and again without considerable loss in the activity.